Access, Utilisation and Quality of Schoolnet Facilities as Predictors of Secondary School Students’ Learning Outcomes in ICT in Southwest, Nigeria (2010)
Information and Communication Technology (ICT) serves as a motivational tool that is capable of influencing the interest of students towards school subjects. In realisation of this, the Federal Government of Nigeria integrated the teaching of computer education in the basic education programme and provided ICT facilities to facilitate its teaching and learning in schools. In spite of these government provisions, the ICT facilities provided in schools are still not adequate. School Net Nigeria (SNNG) a non- governmental organisation provided schools with varieties of ICT facilities for teaching and learning. Meanwhile, the influence of ICT facilities on students’ learning outcomes is yet to be fully realised. This study therefore, examined the extent to which the access, utilisation and quality of the SNNG facilities could predict the students’ learning outcomes (achievement, competence in and attitudes towards) in ICT. The study adopted a survey research design. Multistage sampling technique was used to select the schools involved in the study. The sample consisted of 1100 students (male = 562, female =538) and 20 principals (male = 12, female=8) from 20 schools in four States (Ekiti, Lagos, Ogun and Ondo). Eight instruments were used for data collection; School Checklist, Principals Questionnaire (= 0.62); Students Access to ICT Rating Scale ( =0.65); Students’ Utilisation of ICT Rating Scale ( = 0.65); Students’ Assessment of Quality of ICT Rating Scale (= 0.60); Students’ Achievement in ICT Test (K-R20 = 0.72); Students’ Attitudes to the Use of ICT ( = 0.77) and Students’ Skill acquisition in ICT Test ( = 0.70). Data were analysed using descriptive statistics and multiple regression. The students (95%) and principal (100%) had access and utilised SNNG facilities. As a measure of quality, the rate of replacement was 8%, repair was 0.7% and service was 0.5 % on the SNNG facilities. There was a significant composite effect of access, utilisation and quality of SNNG facilities on achievement in ICT (F (8, 1091) = 13.98, p<0.05) and skill acquisition (F (8, 1091) = 7.74, p<0.05). There was no significant composite effect of access, utilisation and quality of SNNG facilities on attitudes towards ICT use. The most important predictors of achievement (1) and skill acquisition (2) were access to computer (1=3.29, 2  =0.75), quality Internet ( 1  =1.31, 2  = 0.72) and hours the students spent on Internet to do homework ( 1  =3.38, 2 =0.58) all at p= 0.05. Students’ access, utilisation and quality of SNNG facilities increased achievement and skill acquisition in ICT. Therefore, there is need to maintain the quality of SNNG facilities in the existing schools and extend its provision to other schools.